THE IMPLEMENTATION OF ENTREPRENEURIAL ELEMENT IN PRIMARY SCHOOL STANDARD CURRICULUM FOR SPECIAL EDUCATION (KSSRPK) BY SPECIAL EDUCATION TEACHERS. (Proceedings of International Conference on Special Education, 2015)
The purpose of this study is to examine special education teachers' attitudes and their knowledge towards the implementation of entrepreneurships in the Primary School Standard Curriculum (Kurikulum Standard Sekolah Rendah) or KSSR for special education. The survey was carried out in five primary schools integration in Miri, Sarawak and the sample comprised of 50 primary special education teachers (for learning disabilities classes). Besides, this study had identified the problems faced by special education teachers in implementing the entrepreneurship in KSSRPK. This study was conducted using a set of questionnaires and data were analyzed using SPSS version 22. The data were analysed using descriptive statistics such as frequency, percentages and mean. The result shows that, the total average mean score for knowledge on the implementation of entrepreneurship in KSSRPK (MP) is 3.94 and the mean score for the attitude of special education teachers towards entrepreneurship is 3.86. This indicates the knowledge and attitudes of special education teachers are at a high and positive level. The findings also show that lack of times, no specific guidelines, no proper training and exposure on the elements itself and difficulties to accept new changes were among the problems faced by special education teachers during the implementation of the elements of entrepreneurship in their school.